Homestay Tourism in Nepal: Poverty Alleviation Perspectives - Tiwari, Jeevan; Khatiwada, Kabita (International Research Journal of MMC, 2025)
Homestay tourism has emerged as a vital strategy for rural development and poverty alleviation in Nepal, offering a sustainable alternative to traditional tourism models. By allowing tourists to stay with local families, homestay tourism fosters cultural exchange while directly contributing to the livelihoods of host communities. This term paper explores the potential of homestay tourism to reduce poverty in rural Nepal, highlighting its economic, social, and cultural benefits. The paper analyzes how this tourism model empowers marginalized communities, preserves cultural heritage, and promotes inclusive development. Despite its significant contributions, homestay tourism faces challenges, including inadequate infrastructure, lack of training, and insufficient government support. This study argues that with proper investment, training programs, and policy interventions, homestay tourism can serve as a powerful tool for poverty alleviation and sustainable development in Nepal. The findings underline the importance of community participation, public-private partnerships, and eco-friendly practices to maximize the benefits of this innovative tourism model.